Diseño de un juego para prevenir la obesidad infantil y juvenil - Ramón-Fernández, Francisca; Giménez-Chornet, Vicent; Gil-Estevan, María Dolores (Duazary, 2025)
Introduction: Childhood obesity is a health problem. Dietary recommendations do not usually have positive effects, and designing a game to raise awareness among children about adopting healthy habits can be beneficial. Objectives. To evaluate the prototype of a mobile application developed through a multidisciplinary strategy encompassing the educational, healthcare, university, and private sectors. Method: A prototype of the application was designed and piloted at Early Childhood and Primary School (CEIP) Príncipe Don Juan Manuel de Villena, involving students aged 6 to 10 years. The mobile application promoted interactive learning on nutrition and physical activity. Results: Sixty children out of a total of 132 (45.45%) accessed the app. Most participants considered the tool engaging and useful for learning about healthy habits. Conclusions: Digital technologies can play a key role in promoting child health.